Is There a Role for Helicobacter Pylori Infection in Urological Diseases? - Al-Marhoon, Mohammed S (Urology Journal, 2008)
Introduction: Helicobacter pylori (H pylori) infection is a focus of attention nowadays. It has been found to cause gastrointestinal disorders and also extra-intestinal disorders. The aim of this paper is to explore the role of H pylori in urological diseases and to keep urologists up to date in this subject. Materials and Methods: Medline and PubMed were searched from 1950 to December 2007 for the following combined terms: Helicobater pylori together with urology, urological diseases, kidney, kidney cancer, ureter, bladder, bladder cancer, prostate, prostate cancer, benign prostatic hyperplasia, urethra, seminal vesicle, testis, and testicular cancer. Results: Accumulating evidence is appearing in the literature relating H pylori infection to urological diseases. The most obvious is the implication of H pylori in inducing chronic cystitis leading to bladder lymphoma. In addition, some epidemiological studies have shown significant associations between infective chronic prostatitis and prostatic carcinoma. Conclusion: A simple hypothetical model relating H pylori infection to prostate and bladder diseases is proposed to stimulate the collaborative work between the urologists and scientists to explore this field which is underinvestigated to date. If H pylori is found to have a significant role in urological diseases, prevention of bladder and prostate cancers by eradication of H pylori infection may become a reality like what happened in the treatment of peptic ulcer disease and gastric cancer.